Unit nonresponse at the firm level: a cross-border analysis using the IAB-ReLOC data - Veronika Hecht; Nicole Litzel; Johannes Schäffler (Journal for Labour Market Research, 2019)
The labour market effects of foreign direct investments (FDI) are a topic of constant interest. However, research progress is hindered as most datasets applied in research on this topic suffer from selectivity with respect to firm size. To overcome this deficiency a unique dataset that covers the total population of German firms with FDI in the Czech Republic and their Czech affiliates has been created: the IAB-ReLOC data. Based on this dataset, two points of high relevance are addressed in this paper. First, by presenting the generation process of this unique dataset the paper wants to provide guidance for similar cross-border data compilation projects and for researchers working with the data. Second, new insights on unit nonresponse in a firm-level survey are revealed. Based on multi-level logit models, the influence of firm and interviewer characteristics and of FDI features on survey participation is analysed. The main result is that apart from firm size and interviewer involvement, the response behaviour is related to the distance to the German-Czech border and to the strength of the cross-border relationship. What concerns the two latter characteristics, differences between German and Czech firms are identified.
Keywords: C81; C83; F23; 330; Cross-border survey; Czech Republic; FDI; Firm-level survey; Germany; Unit nonresponse